genetic diversity of two Brazilian Vellozia (Velloziaceae) with different patterns of spatial distribution and pollination biology - Franceschinelli, E.V; Jacobi, C.M; Drummond, M.G; Resende, M.F.S (Annals of botany, 2006)
BACKGROUND AND AIMS: The genetic structure and variability of two species of Vellozia (Velloziaceae) with restricted distribution in high-altitude quartzitic fields in south-eastern Brazil were studied. Vellozia epidendroides is short, grows on pebbly or sandy soil, and is pollinated by bees. Vellozia leptopetala is arborescent, grows on rock outcrops, and is pollinated by bees and hummingbirds. Both are self-incompatible and have a short, massive flowering strategy. The study aimed to associate differences in their genetic diversity and structure with their microhabitat distribution and pollination ecology. METHODS: Leaves from 106 and 139 plants of V. epidendroides and V. leptopetala, respectively, were collected from five patches of each species and prepared for electrophoretic analyses. KEY RESULTS: Five enzyme systems could be reliably scored for both species. Vellozia epidendroides showed 100 % of the loci polymorphic for almost all patches. The average number of alleles per locus ranged between 2·2 and 2·4 among patches. The Wright's fixation index (F) for this species was 0·226. A significant {theta}[subscript p] value indicates that there is a reasonable genetic divergence among patches. Vellozia leptopetala presented 47·5 % of polymorphic loci. All levels of P, A, A[subscript p] and of heterozygosities were lower than those of V. epidendroides. Vellozia leptopetala showed high inbreeding within patches. CONCLUSIONS: The relatively high values of genetic diversity indices found for V. epidendroides may be associated with its large and widespread populations. On the other hand, the low values of genetic diversity found for V. leptopetala may be related to physical isolation on outcrops and intensive foraging by territorial hummingbirds, which may hinder gene flow among patches, aggravated by the very restricted seed dispersal characteristic of the genus, that facilitates sibling mating. It is important to stress the need to preserve the specific habitats of these species of Vellozia, in particular those of V. leptopetala that has lower genetic diversity and is restricted to rock outcrop environments.